Pendidikan Agama Hindu dan Budi Pekerti Sebagai Fondasi Pembentukan Karakter Siswa Hindu - Wijaya, Made; Sulastri, Komang; Rianiati, Wayan; Budiani, Kadek; Artiani, Ketut (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the role of Hindu Religious Education and Character Education (Budi Pekerti) as a foundational element in shaping the character of Hindu students in schools. In the midst of modern educational challenges marked by moral decline and the erosion of ethical values, Hindu Religious Education and Budi Pekerti play a strategic role in instilling spiritual, moral, and social virtues. Through core teachings such as Tri Kaya Parisudha (purity of thought, speech, and action), Tri Hita Karana (harmony among humans, God, and nature), and Tat Twam Asi (awareness of the oneness of all beings), students are guided to develop faith, ethical awareness, and noble conduct. This study employs a qualitative descriptive method using literature review and field observation of classroom practices. The findings indicate that the consistent implementation of Hindu Religious Education and Budi Pekerti, both in school and at home, significantly contributes to fostering disciplined, honest, responsible, and empathetic student character. Thus, this subject acts as a primary foundation in forming young Hindu generations who are virtuous, religious, and capable of navigating global dynamics based on dharma values.